2001
DOI: 10.1063/1.1354153
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of carrier localization in Ga1−xInxNyAs1−y/GaAs quantum wells

Abstract: We have investigated by temperature-dependent photoluminescence (PL) spectroscopy as-grown GaInNAs, InGaAs, and GaAsN quantum wells (QWs) embedded in a GaAs matrix. The evolution of the PL peak position and of the PL linewidth shows evidence of a strong carrier localization for the GaInNAs QWs only. The high delocalization temperature, in the 150 K range, indicates the presence of a high density of possibly deep-localizing potential wells. In addition, a higher density of nonradiative recombination centers app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
81
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 21 publications
9
81
1
Order By: Relevance
“…3,[9][10][11][12][13][14][15] Many works have demonstrated that the disorder in the InGaNAs alloy has a strong effect on the carrier motion, and that the radiative recombinations are generally dominated by localized excitons. [11][12][13][14][15] These works also suggest that the microscopic origin of the localized states is related either to the formation of In-N clusters, 11,13,15 or to the well width fluctuations and/or the local strain field induced by the presence of N. 11,14 Ungaro et al 3 have recently demonstrated that semiconductor alloys from the material-GaAsSbN-grown on a GaAs substrate can be used to prepare optical devices that emit light at room temperature in the 1.3-1.55 m wavelength range. 3,9 In particular, 100-Å-thick GaAs 0.825 Sb 0.15 N 0.025 /GaAs quantum wells ͑QWs͒ have demonstrated emission at 1.57 m. 9 In the present study, we investigated the temperature dependence of excitonic recombination in the GaAsSbN/GaAs QWs in the 9-296 K range.…”
Section: Introductionmentioning
confidence: 99%
“…3,[9][10][11][12][13][14][15] Many works have demonstrated that the disorder in the InGaNAs alloy has a strong effect on the carrier motion, and that the radiative recombinations are generally dominated by localized excitons. [11][12][13][14][15] These works also suggest that the microscopic origin of the localized states is related either to the formation of In-N clusters, 11,13,15 or to the well width fluctuations and/or the local strain field induced by the presence of N. 11,14 Ungaro et al 3 have recently demonstrated that semiconductor alloys from the material-GaAsSbN-grown on a GaAs substrate can be used to prepare optical devices that emit light at room temperature in the 1.3-1.55 m wavelength range. 3,9 In particular, 100-Å-thick GaAs 0.825 Sb 0.15 N 0.025 /GaAs quantum wells ͑QWs͒ have demonstrated emission at 1.57 m. 9 In the present study, we investigated the temperature dependence of excitonic recombination in the GaAsSbN/GaAs QWs in the 9-296 K range.…”
Section: Introductionmentioning
confidence: 99%
“…The PL peak reaches its lowest FWHM at 175 K, before increasing again due to the thermalization of the carriers. 17 Also above ϳ175 K, only the FE peak is present and the PL peak redshift is solely associated with the reduction of the band gap with increasing temperature.…”
mentioning
confidence: 97%
“…Any inhomogeneity in thickness or composition manifests itself as an abnormal S-shaped temperature dependence of the PL peak position. This peculiarity, well-known for the quaternary GaInAsN/GaAs material, [23][24][25] originates from the exciton localization effect inside the Sb-rich, quantum dot-like, regions of the quaternary GaInAsSb alloy. 20 The PL measurements were carried out as a function of temperature (14 K-290 K) at different, i.e., high (150 W/cm 2 ) and low (5 W/cm 2 ), excitation intensities (Fig.…”
mentioning
confidence: 94%
“…At low excitation intensity, the S-shaped behavior characteristic of a localization effect at low temperature was clearly visible both for the intrinsic (blue) and the p-i-n sample (red), but this S-shape behavior was not longer visible for the reference InGaAs sample (black). At high excitation intensity, any potential localized states were saturated, resulting in a classical (monotonic) energy variation over the full temperature range and the PL peak energies following the Varshni model 26 (all the parameters E(0), a, and b are given in Table III for all samples): By examining both the excitation intensity variation and the energy difference E loc (T) ¼ E(T) À E PL (T) (where E(T) is the middle-to-high temperature range fit using the Varshni model and E PL (T) is the PL peak energy at low excitation powers 25 ), we extract the carrier localization energies. The 14 K and the maximum localization energies are reported (Table III), together with the full delocalization temperatures.…”
mentioning
confidence: 99%